Pentoxifylline (Vasonit®) – a pathogenetic approach for the correction of cognitive impairment in cerebrovascular diseases. A review - Nataliya V. Titova; Ilya A. Putyatin (Consilium Medicum)
Cognitive impairment is one of the key manifestations of chronic cerebrovascular diseases. Among the factors contributing to their development are microcirculatory disturbances, changes in blood rheological properties, endothelial dysfunction and oxidative stress. This review is devoted to the analysis of the clinical application potential of the nonspecific phosphodiesterase inhibitor pentoxifylline (Vasonit®) in the therapy of patients with chronic cerebral ischaemia in order to correct haemorheological and haemodynamic factors. Data from experimental and clinical studies indicating the possibility and pathogenetic validity of the use of pentoxifylline (Vasonit®) in the complex therapy of cognitive disorders associated with chronic cerebrovascular diseases are considered. The authors describe their own experience of using Vasonit® in a patient with vascular cognitive impairment.